Future Challenges of Nursing in Health System of Iran - Salman Barasteh; Maryam Rassouli; Mohammad Reza Karimirad; Abbas Ebadi; Abbas Ebadi (Frontiers Media S.A., 2021)
Purpose: Nursing development is considered as one of the most important ways to achieve the universal health coverage and sustainable development goals in different countries. Nursing in Iran has the potential to provide services at all levels of universal health coverage. Therefore, planning for nursing in Iran needs to recognize the future challenges. This study aims to explore the future challenges of nursing in the health system of Iran from the perspective of nursing experts.Methods: In this qualitative study, 11 semi-structured interviews were conducted with nursing experts by purposive sampling in 2017-2018. Interviews were recorded and transcribed and framework analysis method was used to analysis the data.Results: The results showed that a favorable future requires planning in three areas of nursing "governance challenges" including centralized nursing stewardship, policy-making and legislation, monitoring and evaluation, and cooperation and communication with other institutions, "inadequacy of professional development with social demands" including community-based nursing, nursing upgrades with disease patterns, expanding home care, expanding care centers, and use of technology, "human resource challenges "including nursing education tailored to the needs of the community, empowering nursing managers, recruiting and retaining nurses, and specialized nursing.Conclusions: A favorable future requires a coherent nursing government, professional development of nursing based on social demands, and enhancing human resources in line with the emerging needs of the future.